Підвищення ефективності управління за рахунок впровадження системи SAP R/3 - Несвітайло, Дар’я; Олійник, Ганна; Грибков, Сергій (Видавництво Львівської політехніки, 2013)
The results of implementation the system SAP R/3 in the holding company "Blitz-Inform" are studied in the work. According to the research was obtained the conclusion about effective implementation and exploitation of the SAP R/3. The system has enabled integration of the all business processes in the holding company "Blitz-Inform" into a single planning, managing and controlling system. That’s ensuring the companies’ management efficiency.
Keywords: система управління підприємством; холдингова компанія; SAP R/3; інформаційні системи та технології